The Pragmatic Study of Speech Act Analysis in Discussion Activities on Speaking Learning - Widiastuti Muchsin (EDUVELOP, 2020)
The research problems of this research is what are the types and functions of speech acts that appear in discussion activities on speaking learning of 3rd semester students of Polytechnic ATI Makassar. The methods in this research is a descriptive qualitative method. The subject of this research is the 3rd semester Politechnic ATI Makassar students in class discussion activities. The results of the study can be described as follows. There are several types of speech acts found. Based on the action objectives of the speaker's perspective, Locutionary act, Illocution act, and perlocutionary act are found. Locutionary speech acts include news, questions and orders. Illocutionary speech acts include assertive, directive, expressive, commissive and declarative illocution